Problematic social media use is associated with poorer attention and increased media multitasking behavior - Siqueira, Sara (Tufts Archival Research Center, 2022)
Examining the relationship between problematic social media use, as a parallel construct to addictive behaviors, and cognitive-related attentional measures.; Thesis (B.S.)--Tufts University, 2022.; Submitted to the Dept. of Psychology.